Cellular phone collateral damage: A review of burns associated with lithium battery powered mobile devices. Issue 4 (June 2016) - Mankowski, Peter J.; Kanevsky, Jonathan; Bakirtzian, Parseh; Cugno, Sabrina
Highlights: Systematic review of burns sustained from cellphone use and there management. Case report of thigh burn sustained secondary to cellphone battery malfunction. Optimization of cellphone safety with discussion of burn eliciting factors. Abstract: Aim: The spontaneous destruction of lithium battery powered cellphones has raised concern about the safety of these devices. We present a case report and review of the literature of burn injuries sustained in association with cellular phone usage. Methods: A Medline search was performed to identify articles describing cellular phone associated thermal injuries using key search words including "burn, " "burn injury, " "cellular phone, " "cellphone, " "thermal injury, " and "telephone." Articles were reviewed for etiology, location, severity and treatment. We also present a case of a burn to the upper thigh resulting from cellular phone battery malfunction. Results: Six case reports were identified detailing burn injuries obtained from cellphone use. Half of these cases occurred from battery malfunction with second degree being the most common severity. All cases were managed conservatively except one case, which required excision and primary closure. Conclusion: Lithium powered cellular phones are susceptible to overheating and destruction from inadequate heat dissipation during thermal runaway. This process can be initiated by local short-circuiting from direct contact with a low resistance conductor such as keys or coins. We reinforce the importance of safe cell phone battery practices including avoiding overcharging and direct skin exposure to minimize thermal injury risk.